Molecular Characteristics and Pathogenicity of Porcine Epidemic Diarrhea Virus Isolated in Some Areas of China in 2015–2018 - Yu, Linyang; Liu, Yanling; Wang, Shuangyun; Zhang, Leyi; Liang, Pengshuai; Wang, Lei; Dong, Jianguo; Song, Changxu (Frontiers in Veterinary Science, 2020)
Since 2010, Porcine epidemic diarrhea virus (PEDV) has caused severe diarrhea disease in piglets in China, resulting in large economic losses. To understand the genetic characteristics of the PEDV strains that circulated in some provinces of China between 2015 and 2018, 375 samples of feces and small intestine were collected from pigs and tested. One hundred seventy-seven samples tested positive and the PEDV-positive rate was 47.20%. A phylogenetic tree analysis based on the entire S gene showed that these strains clustered into four subgroups, GI-a, GI-b, GII-a, and GII-b, and that the GII-b strains have become dominant in recent years. Compared with previous strains, these strains have multiple variations in the SP and S1-NTD domains and in the neutralizing epitopes of the S protein. We also successfully isolated and identified a new virulent GII-b strain, GDgh16, which is well-adapted to Vero cells and caused a high mortality rate in piglets in challenge experiments. Our study clarifies the genetic characteristics of the prevalent PEDV strains in parts of China, and suggests that the development of effective novel vaccines is both necessary and urgent.